ANALISIS KEMAMPUAN MENULIS PANTUN SISWA KELAS V B SDN 1 MIDANG LOMBOK BARAT TAHUN PELAJARAN 2020/2021 - Husnul Khadijah; Siti R. H. Intiana; Husniati Husniati (Program Studi PGSD, FKIP, Universitas Mataram, 2021)
This study aims to determine the ability of grade V B students of SDN 1 Midang in writing poetry for the 2020/2021 school year. The results of this study are expected to be useful for students, teachers and other researchers. This research is a descriptive study with quantitative methods. The subjects in this study were all students totaling 25 students consisting of 10 male students and 15 female students. Data collection techniques using documentation and interviews. Data analysis using descriptive analysis techniques. Based on the results of data analysis, the ability to write pantun in the very good category was 15 students with a percentage of 60%. The ability to write rhymes in the good category was 3 students with a percentage of 12%. The ability to write pantun who got sufficient category was 4 students with a percentage of 16%. And the ability to write pantun who got the less category was 3 students with a percentage of 12%. Thus, according to the calculation of the mean value, it can be concluded that the students' ability to write poetry in grade V B SDN 1 Midang is in good category with an average score of 79.